Level crossing lights for model railroads / Azizah Abdullah and Fadzillah Ahmad - Abdullah, Azizah; Ahmad, Fadzillah (1989)
With the extra touch of realism to the model railway layout and an electronic innovation, this project is a very realistic display for a model train layout. It can provide three traffic lights for a road intersection, a level crossing and a pedestrian crossing which is switched on and off as the train passes.